2018
DOI: 10.1016/j.abrep.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic variations in the relationship between multiple stress domains and use of several types of tobacco/nicotine products among a diverse sample of adults

Abstract: IntroductionFinancial strain and discrimination are consistent predictors of negative health outcomes and maladaptive coping behaviors, including tobacco use. Although there is considerable information exploring stress and smoking, limited research has examined the relationship between patterns of stress domains and specific tobacco/nicotine product use. Even fewer studies have assessed ethnic variations in these relationships.MethodsThis study investigated the relationship between discrimination and financial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
5
1
Order By: Relevance
“…Considering that health insurance is the gateway to healthcare and these demographic and SES factors are commonly correlated with health status (18,43,(65)(66)(67), these variables were selected in order to analyze the unique relationship between financial difficulties and continuous mental and physical health variables. While much of the previous research would suggest that binge drinking is positively associated with financial difficulties, especially for AA samples (8,9,11), the findings did not indicate an association between financial difficulties and binge drinking. This may be due to the high percentage of participants who did not drink at all in our sample (65.1%).…”
Section: Adjusted Correlates Of Financial Difficultiescontrasting
confidence: 70%
See 1 more Smart Citation
“…Considering that health insurance is the gateway to healthcare and these demographic and SES factors are commonly correlated with health status (18,43,(65)(66)(67), these variables were selected in order to analyze the unique relationship between financial difficulties and continuous mental and physical health variables. While much of the previous research would suggest that binge drinking is positively associated with financial difficulties, especially for AA samples (8,9,11), the findings did not indicate an association between financial difficulties and binge drinking. This may be due to the high percentage of participants who did not drink at all in our sample (65.1%).…”
Section: Adjusted Correlates Of Financial Difficultiescontrasting
confidence: 70%
“…A systematic review of the literature by Richardson and colleagues revealed a number of findings indicating a relationship between financial concerns and the likelihood to smoke (8). Recent findings indicate financial difficulties increase the risk of tobacco/nicotine use, and this relationship is especially strong for AA populations (11). Furthermore, financial difficulties can influence smoking cessation such that pre-quit financial difficulties are associated with more severe withdrawal symptoms which in turn reduces the likelihood of smoking abstinence (12,13).…”
Section: Mental and Physical Correlates Of Financial Difficultiesmentioning
confidence: 99%
“…The present study is also one of the first to examine the relationship between discrimination and e-cigarette. A recent study found that more frequent discrimination was directly associated with higher odds of combustible tobacco use in the overall sample and among Black Americans, but higher odds of e-cigarette use in the overall sample and among White Americans (Rogers et al, 2018). Moreover, we previously found that persons with PD and lifetime mental health conditions were more likely to be current or daily e-cigarette users (Spears et al, 2017, 2018, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although much of the research has focused mainly on racially minoritized individuals’ coping with interpersonal ethnic–racial discrimination through alcohol, cannabis, opiates, and other illicit drug use (Pascoe et al, 2022), some research associates increased incidences of licit substances such as tobacco and other nicotine products has also been established (Kendzor, Businelle, Reitzel, Rios, et al, 2014; Rogers et al, 2018). Rogers et al (2018) discovered significant dose–response relationships between increased experiences of IERD and increased usage of combustible and electronic tobacco/nicotine products among a sample of racially diverse adults. Moreover, increased IERD reduced the likelihood of achieving 7-day abstinence among tobacco users attempting tobacco cessation (Kendzor, Businelle, Reitzel, Castro, et al, 2014).…”
Section: Effects Of Ierd On Tobacco Usementioning
confidence: 99%